Modern Japanese prints : - Statler, Oliver (Charles E. Tuttle, 1967)
This book is not only an excellent introduction, well illustrated to modern Japanese prints, it is also a loving record of the artists who have created this beauty... At least a dozen of the living men discussed are very wonderful artists in the full world-stream of art.